THE IMPACT OF MINING BUSINESS LICENSE POLICY IN SOUTHEAST SULAWESI AFTER THE ENACTMENT OF LAW NUMBER 23 OF 2014 - La Ode Wahiyuddin; Sinta Nigrum; Yogi Suprayogi (Journal Publicuho, 2022)
This study aims to examine in depth the impact of IUP policy This research was designed in the form of a qualitative descriptive study. Data collection is done through interviews, observation, and documentation. The IUP policy, when transferred to the provincial level, was not effectively implemented; it showed the difficulty in coordinating and synchronizing by the Southeast Sulawesi Provincial Government and the Regency Government. Moreover, the Southeast Sulawesi area consists of 15 districts and 2 cities and has many islands which are large enough so that the guidance and supervision carried out are nonoptimal. The refore the IUP policy can be implemented if it is strengthened by strict rules by not only transferring authority but also followed by clear transitional rules and the need for political will both the central and regional governments in overseeing mining affairs.